Cryo-assisted nitrogen treatment for the fabrication of nanoengineered, mixed transition metal oxide anode from ınorganic domestic waste, for lithium-ion batteries - Ashraf, Humza; Karahan, Billur Deniz (My University, 2024)
A novel method for the fabrication of nanoengineered, mixed transition metal oxide anode active material is proposed based on implementing liquid nitrogen treatment during the chemical precipitation process, for the first time in open literature. Such interference in the precipitation is believed to change the surface energy of the nuclei leading to differentiation in the growth process. To exemplify this hypothesis with an environmentally friendly approach, kitchen scourer pads, an existing waste, are used as a starting material instead of using a mixture of primary quality metals’ salts. Therefore, in this study, firstly, an optimization is realized to leach the scouring pad with 100% efficiency. Then, by applying a conventional chemical precipitation to this leachate at pH 5.5, Sample 1-P is produced. Herein, innovatively liquid nitrogen treatment is carried out during the chemical precipitation to produce Sample 2-P. Lastly, these precipitates (Samples 1-P, 2-P) are calcinated in the air to form mixed transition metal oxide powders: Samples 1 and 2, respectively. Structural, chemical, and morphological characterizations are carried out to examine the effect of liquid nitrogen treatment on the powders’ properties. To discuss the effect of nitrogen treatment on the electrochemical performances of the anode active materials (Sample 1 and Sample 2), galvanostatic tests are realized. The results show that Sample 2 demonstrates a higher 1st discharge capacity (1352 mAh/g) and retains 62% of its performance after 200 cycles when 50 mA/g current load is applied. Moreover, this electrode delivers around 500 mAh/g at 1 A/g current load. The remarkable cycle performance of Sample 2 is believed to be related to the superior chemical, structural, and physical properties of the electrode active material. Graphical Abstract: (Figure presented.)
Keywords: Leaching; Liquid Nitrogen Treatment; Mixed Transition Metal Oxide; Resources Recovery From Wastes; Waste-To-Energy Storage